2021
DOI: 10.1002/jbm4.10542
|View full text |Cite
|
Sign up to set email alerts
|

Health Effects of Calcium: Evidence From Mendelian Randomization Studies

Abstract: Calcium is widely used in conjunction with vitamin D to prevent osteoporosis. The use of calcium supplementation is also promoted for its potential benefits in lowering the risk for metabolic syndromes and cancers. However, the causal link between calcium and various health outcomes remains unclear. This review focuses on the evidence from twenty-four Mendelian randomization studies that were designed to minimize bias from confounding and reverse causation. These MR studies evaluated the effect of lifelong gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 90 publications
(163 reference statements)
1
2
0
Order By: Relevance
“…(~0.1 mmol/L) was associated with a 25% increase in the risk of myocardial infarction (21), very similar to the effects found in the Bolland meta-analyses (19,20). Multiple other Mendelian randomisation studies have reproduced this finding (22). These findings are supported by a large body of observational data showing an association between serum calcium concentration and subsequent risk of cardiovascular events (23).…”
Section: Vitamin D and Calciumsupporting
confidence: 68%
“…(~0.1 mmol/L) was associated with a 25% increase in the risk of myocardial infarction (21), very similar to the effects found in the Bolland meta-analyses (19,20). Multiple other Mendelian randomisation studies have reproduced this finding (22). These findings are supported by a large body of observational data showing an association between serum calcium concentration and subsequent risk of cardiovascular events (23).…”
Section: Vitamin D and Calciumsupporting
confidence: 68%
“…These findings are in line with recent Mendelian randomization studies. These studies take a genetic epidemiological approach to estimate causality and have suggested a positive causal influence of transient increases in serum calcium on increased cardiovascular disease risk, especially for myocardial infarction (MI) [20][21][22][23]. However, this increase in cardiovascular disease risk was not observed with higher intake of dietary calcium [24].…”
Section: Skeletal and Extraskeletal Effects Of Calcium And Vitamin Dmentioning
confidence: 99%
“…There is still uncertainty regarding the benefits of CaDs, although many studies have been conducted, including epidemiological studies, metaanalyses, and Mendelian randomization analyses [1,[13][14][15]. However, most studies included only Caucasians, who generally consume moderateto-high amounts of dietary calcium and have a relatively high body mass index (BMI), which potentially limits the generalizability of their results to other populations [4,16].…”
Section: Introductionmentioning
confidence: 99%